Retinoic acid-loaded polymeric nanoparticles induce neuroprotection in a mouse model for Parkinson's disease - Esteves, Marta; Cristóvão, Ana C.; Saraiva, Tatiana; Rocha, Sandra M.; Baltazar, Graça; Ferreira, Lino; Bernardino, Liliana (Frontiers in Aging Neuroscience, 2015)
Retinoic acid (RA) plays an important role in the commitment, maturation and survival of neural cells. Recently, RA was pointed as a therapeutic option for some neurodegenerative diseases, including Parkinson’s disease (PD). The administration of RA has been defying, and in this sense we have previously developed novel RA-loaded polymeric nanoparticles (RA-NPs) that ensure the efficient intracellular transport and controlled release of RA. Herein, we show that nanoformulation as an efficient neuroprotective effect on dopaminergic (DA) neurons in the 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP) induced mouse model for PD. The results showed that the RA-NPs administration induced a significant reduction of DA neuron loss in the substantia nigra (SN) as well as their neuronal fiber/axonal innervations in the striatum. Furthermore, we observed an increase in the expression levels of the transcription factors Pitx3 and Nurr1 induced by RA-NPs, showing its supportive effect on the development and functional maintenance of DA neurons in PD. This is the first study showing that RA-NPs can be an innovative strategy to halt the progression of PD pathogenesis, suggesting that this nanoformulation could be of particular interest for the development of new approaches for PD therapeutics.